Art and Research - Contemporary Challenges - Ciobotaru, Anca Doina; Enescu, George (De Gruyter, 2020)
In the artistic / vocational academic education field, a phrase like "scientific research" generates several controversies; however, they can be the roots of interdisciplinary approaches, through which to build bridges between concern and research. The conference "Art and Research - contemporary challenges" aims, also through the published volume, to disseminate the results of research undertaken within the project Art and research - contemporary challenges (CNFIS-FDI-2020-0537). Held between the Doctoral Schools and Research Centers of George Enescu National University of Arts, from Iasi, the conference addresses doctoral students and doctoral coordinators, as well as all university teachers or masters interested in the topic of art interdisciplinarity, use of creative methods and critical tools. Three directions are pursued, namely Theater, Music and Visual Arts, out of the desire to find both common points and to create the possibility for young researchers to meet, to know the directions and concerns in the field of arts research and to realize on future teams. Both the Conference and the resulting volume of articles are aimed at international openness, being published on international databases. Therefore, the impact would be important and not limited to the local perimeter.